QUALITATIVE & RHEOLOGICAL STUDY FOR SORGHUM FLOUR AS A PARTIAL SUBSTITUTE TO WHEAT FLOUR - Mohammad Wajeeh Zainnulabideen (Mesopotamia Journal of Agriculture)
Gross Composition, Physical, Chemical and Rheological Properties for three varieties of certified local cultivars of Sorghum ( Sorghum bicolor L.Mocnch) were studied . Sorghum varieties significantly varied (P<0.05) in most of their chemical content . However protein content was 6.43, 7.87 and 9.94% and Phytic acid content was 0.340 ,0.273 and 0.288 % for Rabh , Enkath and Kafir, respectively . While tannin content was 0.53, 0.47 and 0.53% for Rabh, Enkath and Kafir respectively. Chemical content for Sorghum Flour also varied between these varieties depending upon their flour extraction. Increasing Sorghum Flour substitution at 10, 20, 30 and 40% in composite flour increased Amylogragh gelatinization temperature , maximum viscosity which were 64.5C & 380,0 B.U, respectively for wheat flour while it were 72.75 and 1055,0 B.U respectively for sorghum flour, Farinograph arrival time , development time ,mixing tolerance time also increased which was indicated to weakness of dough, Extensograph resistant / Extension increased due to alteration of dough development and fermentation gas pressure. On the contrary , increasing Sorghum Flour substitution decreased Farinograph water absorption ,stability time, decline time, Extensograph maximum resistant ,Extension and energy (area ).Enkath was the identical variety among them which had the most acceptance by taste panel.